2021
DOI: 10.3389/fonc.2021.644165
|View full text |Cite|
|
Sign up to set email alerts
|

Contrast-Enhanced CT-Based Radiomics Analysis in Predicting Lymphovascular Invasion in Esophageal Squamous Cell Carcinoma

Abstract: ObjectivesTo develop a radiomics model based on contrast-enhanced CT (CECT) to predict the lymphovascular invasion (LVI) in esophageal squamous cell carcinoma (ESCC) and provide decision-making support for clinicians.Patients and MethodsThis retrospective study enrolled 334 patients with surgically resected and pathologically confirmed ESCC, including 96 patients with LVI and 238 patients without LVI. All enrolled patients were randomly divided into a training cohort and a testing cohort at a ratio of 7:3, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
(92 reference statements)
2
9
0
Order By: Relevance
“…However, lymphovascular invasion can be diagnosed only via postoperative histopathology, and preoperative prediction is extremely di cult [22]. A previous report also indicated that enhanced CT is a potential candidate for predicting lymphovascular invasion, although the study subject was not limited to super cial SCC but also included advanced SCC [22]. The bene t of FDG PET/CT for predicting lymphovascular invasion has been described in lung cancer, hepatocellular carcinoma, and colon cancer; [23][24][25] however, it has been poorly studied in super cial ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, lymphovascular invasion can be diagnosed only via postoperative histopathology, and preoperative prediction is extremely di cult [22]. A previous report also indicated that enhanced CT is a potential candidate for predicting lymphovascular invasion, although the study subject was not limited to super cial SCC but also included advanced SCC [22]. The bene t of FDG PET/CT for predicting lymphovascular invasion has been described in lung cancer, hepatocellular carcinoma, and colon cancer; [23][24][25] however, it has been poorly studied in super cial ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Many texture features are unstable in different reconstruction algorithms, while GLevNonU is one of the most repetitive radiomics features showing good stability. The GLevNonU value increases with the tumor heterogeneity, which is related to tumor invasion, treatment response, and prognosis ( 28 ). In this study, we found that the Z_GLevNonU, 45dgr_GLevNonU, and 135dr_GLevNonU values of the BMPTs were statistically larger than those of the BPTs, indicating that the gray-level distribution was more heterogeneous in BMPTs on DCE-MR images, compared with BPTs.…”
Section: Discussionmentioning
confidence: 99%
“…All patients who participated in this study underwent appropriate breathing exercises, and a 64‐bit multi‐detector spiral CTA scanner was used to scan all images. All patients were placed in the supine position with the head facing forward and the hands above the head, and either the chest or the upper abdomen was scanned during the CTA examination 22 . Typically, a traditional CTA scan is performed first, followed by intravenous injection of contrast medium using a syringe pump 23 .…”
Section: Methodsmentioning
confidence: 99%